ATP depletion plays a pivotal role in self‐incompatibility, revealing a link between cellular energy status, cytosolic acidification and actin remodelling in pollen tubes. Issue 5 (23rd July 2022) - Wang, Ludi; Lin, Zongcheng; Carli, José; Gladala‐Kostarz, Agnieszka; Davies, Julia M.; Franklin‐Tong, Vernonica E.; Bosch, Maurice
Summary: Self‐incompatibility (SI) involves specific interactions during pollination to reject incompatible ('self') pollen, preventing inbreeding in angiosperms. A key event observed in pollen undergoing the Papaver rhoeas SI response is the formation of punctate F‐actin foci. Pollen tube growth is heavily energy‐dependent, yet ATP levels in pollen tubes have not been directly measured during SI. Here we used transgenic Arabidopsis lines expressing the Papaver pollen S ‐determinant to investigate a possible link between ATP levels, cytosolic pH ([pH]cyt ) and alterations to the actin cytoskeleton. We identify for the first time that SI triggers a rapid and significant ATP depletion in pollen tubes. Artificial depletion of ATP triggered cytosolic acidification and formation of actin aggregates. We also identify in vivo, evidence for a threshold [pH]cyt of 5.8 for actin foci formation. Imaging revealed that SI stimulates acidic cytosolic patches adjacent to the plasma membrane. In conclusion, this study provides evidence that ATP depletion plays a pivotal role in SI upstream of programmed cell death and reveals a link between the cellular energy status, cytosolic acidification and alterations to the actin cytoskeleton in regulating Papaver SI in pollen tubes. Abstract : See also the Commentary on this article by Cheung, 236 : 1625–1628 .